Pengaruh Kualitas Produk Dan Harga Terhadap Minat Beli Konsumen Mie Gacoan Kota Probolinggo - rahayu, sri; Fahrudin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Competition in the culinary industry encourages business actors to continuously improve product quality and set competitive prices to attract consumer purchase intention. This study is based on the growing competition where consumers consider not only the price but also the overall quality of the products offered. The purpose of this study is to determine the extent to which product quality and price influence the purchase intention of Mie Gacoan consumers in Probolinggo City. A quantitative approach with a causal associative research design was used. Data were collected through questionnaires distributed to 109 respondents using purposive sampling. The data were then analyzed using multiple linear regression to test the partial and simultaneous effects of the independent variables on the dependent variable. The results showed that product quality had a positive and significant effect on purchase intention. Meanwhile, price had a negative but significant effect. Simultaneously, both variables had a significant effect on purchase intention. These findings indicate that consumers prioritize consistent quality over merely affordable prices. The results provide strategic implications for culinary business actors to maintain product quality and set prices in line with consumers' purchasing power, supporting efforts to foster consumer loyalty and increase competitiveness in the local market.